Kolaborasi Sosial dalam Identifikasi Fakir Miskin: Studi Peran Ketua RT dan Panitia Zakat di Pedesaan - Muhammad Haris (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2025)
This study aims to understand the form and dynamics of social collaboration between the RT Head and the zakat committee in the process of identifying the poor in rural areas. The approach used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results of the study indicate that collaboration between the two local actors is based on social networks and community trust, but is also full of subjectivity in determining aid recipients. Although this practice strengthens sensitivity to local conditions, there are still limitations in transparency and potential for social bias. This study emphasizes the importance of combining local knowledge with a more accountable and inclusive formal identification system.